Pengembangan front end web sistem informasi akademik pesantren al-husna (sisna) menggunakan metode user centered design - Naimatul Mutamimah (Fakultas Ilmu Komputer, 2025)
This thesis research focuses on the development of front end web academic information system of pesantren al-husna (SISNA) using user centered design method. This pesantren has limitations to design an application display that is responsive, user friendly, and in accordance with user needs. As for The purpose of this research is to produce a development of a front end web application of the al-husna female pesantren information system using the user centered design method.. The application development process starts from understanding user context, identifying functional and non-functional requirements, designing a design solution, then implementing the front end display using HTML, CSS, and the React library. the last step is evaluating the appearance of the system using the sus method (system usability scale). Based on the results of questionnaires that have been distributed to 40 prospective users among 20 students, 13 teachers, and 7 administrators, get an average SUS score of “82”. With an acceptability score of “acceptable”, the grade score is ‘B’, and the adjective rating is“excellent”. This means that the front end web application of the pesantren academic information system al-husna can be well received by prospective users.
Reupload file repository 13 Maret 2026_Ratna
Keywords: Front end; user centered design; system usability scale; web development; information system.